Analyzing and Modeling of Water Transport Phenomena in Open-Cathode Polymer Electrolyte Membrane Fuel Cell - Wei-Wei Yuan; Kai Ou; Seunghun Jung; Young-Bae Kim (Applied Sciences, 2021)
Water management is one issue that must be surpassed to ensure high membrane proton conductivity and adequate reactant transport in the membrane-electrode assembly (MEA) simultaneously. A well-designed water management system is based on a comprehensive understanding of water transport in the inner part of the polymer electrolyte membrane (PEM) fuel cell. In this work, the water transport phenomena in the MEA PEM fuel cell are analyzed by using a mathematical model. The transport of diluted species interface is used to model the transport of water in the ionomer phase in the catalytic layer and the membrane domains. The molecular flux of water is defined using Nernst–Planck equations, including migration and Fickian diffusion using parameters obtained experimentally for diffusivity and mobility based on water drag for a fully humidified membrane. The proposed model 1D model includes anode gas channel, cathode gas channel, anode gas diffusion layer (GDL), cathode GDL, anode catalyst layer, cathode catalyst layer, and proton exchange membrane. Water activity, ionomer conductivity, and output voltage are predicted by changing the humidity on the anode side of the fuel cell.